Corneal Epithelial Damage Following Bacillus thuringiensis Bioinsecticide Exposure in Wistar Rats - Komariah, Cicih; Astuti Setyawardani; Al Kamal, Ahmad Asrori; Nurul Amin, Aldi Nawaf; Hurriyyah, Hashinatul; Ulil Albab, Fathiah; Daeng Ndiko, Siti Aminah (Jurnal Kedokteran Brawijaya, 2026)
Approximately 2% of bioinsecticides for pest control are biopesticides; 90% are Bt bioinsecticides, typically in spray form. Bt solution is acidic and may cause ocular surface damage. This study is conducted to determine the Bt exposure method and concentration that might cause corneal ocular surface damage. This study was performed on Wistar rats anesthetized with 75mg/kg BW ketamine intraperitoneally, with these four treatments: 1. Bt Dipel WG solution exposure by filter paper with 0.5g/L, 1g/L, 2g/L, and 4g/L concentrations for 1 minute; 2. Bt Dipel WG solution exposure by filter paper with 6g/L, 8g/L, and 10g/L concentrations for 1 minute; 3. 3mL Bt Dipel WG solution exposure by drops for 2 minutes with 6g/L, 8g/L, and 10g/L concentrations; and 4. 3mL Bt Dipel WG solution exposure by drops for 2 minutes with 6g/L, 8g/L, and 10g/L concentrations and eyelid closure for 30 minutes. Treatments 1, 2, and 3 were performed for 3 days; treatment 4 was performed for 7 days. Exposures were made on different rats. Corneal defects were identified using fluorescent liquid and blue penlight. Corneal ocular surface damage was evident in two Wistar rats exposed to 10g/L Bt Dipel WG solution drops in the cornea with 30 minutes of eyelid closure for seven consecutive days. Bt bioinsecticide may cause corneal defects with exposures of 10 g/L and 30 minutes of eyelid closure for seven days.